Determinants of endurance exercise performance - Coyle, E. (1999)
Performance in endurance events is typically evaluated by the power or velocity that can be maintained for durations of 30 minutes to four hours. The two main by-products of intense and prolonged oxidative metabolism that can limit performance are the accumulation of hydrogen ion (i.e.; lactic acidosis) and heat (i.e.; hyperthermia). A model for endurance performance is presented that revolves around identification of the lactate threshold velocity which is presented as a function of numerous morphological components as well as gross mechanical efficiency. When cycling at 80 RPM, gross mechanical efficiency is positively related to Type I muscle fiber composition, which has great potential to improve endurance performance. Endurance performance can also be influenced by altering the availability of oxygen and blood glucose during exercise. The latter need forms the basis for ingesting carbohydrate at 30-60 grams per hour during exercise. In laboratory simulations of performance, athletes fatigue due to hyperthermia when esophageal is approximately 40°C, in association with near maximal heart rate and perceived exertion. It is likely that the central nervous system is involved in the aetiology of fatigue from hyperthermia. Dehydration during exercise promotes hyperthermia by reducing skin blood flow, sweating rate and thus heat dissipation. The combination of dehydration and hyperthermia during exercise causes large reductions in cardiac output and blood flow to the exercising musculature, and thus has a large potential to impair endurance performance. Endurance performance is optimized when training is aimed specifically at developing individual components of the model presented and nutritional supplementation prevents hypoglycemia and attenuates dehydration and hyperthermia. Indeed, the challenge at the transition to a new millennium is to synergistically integrate these physiological factors in training and competition. In: 5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999 Sydney 31 October -5 November 1999